The effect of social (family and peers) support on entrepreneurial intentions of undergraduates at Universiti Pendidikan Sultan Idris (UPSI) - Leong, Ching Yee (Tanjong Malim, 2024)
The effect of social (family and peers) support on entrepreneurial intentions of undergraduates at Universiti Pendidikan Sultan Idris (UPSI) by Leong, Ching Yee